- #1

bernhard.rothenstein

- 991

- 1

p=g(u')g(V)m(0)(V+u')=g(u')g(V')E(0)(V+u')cc

E=g(u')g(V)E(0)(1+Vu'/cc)

I consider that such a presentation presents some (pedagogical) advantages showing clearly what observers from the I frame measure in the case when u'=0 and when u' and V are both equal to zero.

Even if I know that the concept of relativistic mass is

*persona non grata*on the Forum I would also suggest for the relativistic mass

m=g(u')g(V)E(0)(1+Vu'/cc)=g(u')g(V)m(0)(1+Vu'/cc).

The oppinion of those who teach or learn special relativity theory is highly appreciated of course in the spirit of

**sine ira et studio**